Comorbidity and impact of bronchial asthma to gastroesophageal reflux disease in children - Y.V. Кarpushenko; Т.V. Frolova; N.M. Drobova; О.М. Ashcheulov (Сучасна педіатрія: Україна)
Gastroesophageal reflux disease (GERD) is a highly comorbid disease with bronchial asthma (BA). The relationship between GERD and BA is complicated and controversial.